Immigrants and foreigners in Central and Eastern Europe during the twentieth century
1 online resource
Keywords: "Immigrants and Foreigners in Central and Eastern Europe during the Twentieth Century challenges widespread conceptions of central and eastern European countries as merely countries of origin, and sheds light on the experience of immigration and the establishment of refugee regimes at different stages in the history of the region"--